Paradoxos das noções jurídicas de pessoa e liberdade: o princípio da proporcionalidade e a época das imagens dos Direitos Humanos - Pereira, Joaquim Eduardo (2015)
The Universal Declaration of Human Rights is the result of a joint effort, at least with regard to the West, to give a response to the atrocities committed in the Second World War and to the trivialization of violence there reached its peak. We intend to show how the need for such response may not correspond necessarily to concern for others, with the lives of others. And also like the notions of personality and freedom, while the subjectivity structures, is insufficient not only to correct the law and give it a foundation, as it is not suitable as a means to achieve a true understanding of what is properly the humanity of man. It is not, however, simply reject the Human Rights Declaration, but understand his fictional character and as a real possibility to deal with the law and violence should not stand in the dignity of the human person, but on the principle of proportionality